Synthesis and Implementation (In STM8S) of Phased Circular Antenna Arrays Using Taguchi Method - Nadhem Nemri; Hani Wadie Badri; Ridha Ghayoula; Hichem Trabelsi; Ali Gharsallah (Institute of Advanced Engineering and Science, 2016)
This paper is aimed at assessing the effectiveness of the phase-only control strategy based on a customized Taguchi method when applied to Uniform Circular Arrays (UCA). The objective of this paper consists to contribute the main lobe optimization of the smart antenna using Taguchi's method. We used the cited method in order to determine phase's weights for each element of the circular antenna array in order to steer the principal lobe from -65° to 65° covering all angular space. After that, we made an electronic platform using the microcontroller STM8S in order to implement an intelligent system. The architecture of this work had used a digital phase shifters, a demodulator AD8347, a modulator AD8349, an array antenna, cards STM8S-Discovery.